Design and production of peptide-based scaffolds for bioengineering applications - Lychko, Iana (2018)
Protein- and peptide-based affinity reagents have demonstrated a great potential in different bioengineering fields, including the identification and capture of target molecules with applications in purification and sensing. This work focused on the study and production of cyclic β-hairpin peptides and Odorant-Binding Proteins (OBPs) as affinity reagents for application in bioseparation and biosensing, respectively. Two cyclic β-hairpin peptides (cyclic-M3 and cyclic-M9) were previously designed by docking, as potential affinity reagents for phosphorylated peptides. Here, cyclic-M3 and cyclic-M9, as well as a control peptide cyclic-M0 were chemically synthetized and characterized through Mass Spectrometry, analytical HPLC and Circular Dichroism. To evaluate the binding affinity of cyclic peptides towards several phosphorylated peptides, binding studies were performed in solution, by the MicroScale Thermophoresis technique. Cyclic-M3 and cyclic-M9 interact with a phosphorylated peptide GK14P with KA of 1.0 mM-1 and 1.34 mM-1, respectively. In addition, the cyclic peptides were selective for the phosphorylated moieties. Two rat OBPs (OBP2 and OBP3) were selected as experimental models for developing affinity reagents capable to detect specific volatile organic compounds (VOCs). Binding studies published until May 2018 reporting proteins selectivity and structural information were used to analyze structural characteristics involved in the natural binding of VOCs. Due to the lack in structural information for OBP2, homology modeling was employed to set a 3D structure. OBPs bind molecules with variable chemical and structural features mostly though hydrophobic interactions. However, the presence of determinant amino acid residues in the binding pockets increase the specificity of these proteins against VOCs. Both OBPs were successfully produced as soluble proteins using the E. coli expression system for further purification and biochemical characterization.